Directional Modulation from a Wrist-Wearable Compact Antenna - Zandamela, Abel Abdul; Marchetti, Nicola; Narbudowicz, Adam (IEEE, 2022)
This work proposes compact multiport antennas for directional modulation (DM) on wrist-wearable devices to improve the secrecy and privacy of the transmitted data. The DM performance is investigated using the antenna in free-space and with a human forearm-phantom. The system achieves a low Bit Error Rate (BER) < 10^(-1) with 44° beamwidth, in a unique steerable secure direction over the entire azimuth plane. Full-wave simulations including the phantom at 5 GHz show realized gains of up to 4.26 dBi. The specific absorption rate is below the standard limits, with maximum values of 0.487W/kg and 1.42W/kg for the wrist-worn and next-to-mouth conditions, respectively.
16th European Conference on Antennas and Propagation
PUBLISHED
Madrid, Spain
Keywords: Wrist-wearable antennas; Internet of Things; Directional Modulation; Compact IoT Devices; Physical Layer Security; Telecommunications; Directional Modulation; Information Technology; Wearable Devices; Wireless Physical Layer Security; Wireless systems, Radio technology